Cyber-Threat Analysis of a UAV Traffic Management System for Urban Airspace - Sidorov, Vasily (2017)
Unmanned air traffic management system (UTMS) and the eco-system around it can be viewed as a large, complex, loosely-coupled cyber-physical system with flows of digital and analog data, sensors that collect data, and actuators that act upon data. As such, the eco-system has a large cyber-attack surface, which, if penetrated, can cause serious damage and even casualties. We present a comprehensive analysis of the cyberattack surface of the UTMS and UAV traffic eco-system. In this work, we propose an architectural framework for a UTM ecosystem; define a cyber threat; identify the essential assets of the system and their properties that need to be protected. This work was done in the context of managing traffic of UAVs in Singapore’s urban airspace.